The Effect Of Accounting Information System Quality And Service Quality On BRI Mobile Banking Application User Satisfaction - Ratu, Ratu; Baiq Anggun Helindri Lestari (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to investigate the influence of accounting information systems and service quality on user satisfaction with the BRI Mobile application. It utilizes primary data from 89 active students enrolled in the Accounting Study Program at the University of Mataram, analyzed through multiple linear regression using PLS 4 statistical software. The results reveal that both high-quality accounting information systems and excellent service have a significant positive impact on student satisfaction with the BRI Mobile application. This research emphasizes the importance of enhancing service quality in mobile banking applications and developing effective accounting information systems. For accounting students, the findings highlight the necessity of a comprehensive understanding of how accounting information systems are applied in digital banking, as well as the importance of technological skills to navigate workplace challenges. As a result, banks can continually improve their services, while students will be better equipped to contribute to the accounting and banking sectors.